OLED display crack repairing material and repairing process
Patent Information
- Application Number
- CN202610807187.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-27
AI Technical Summary
然而,在实际使用中,OLED显示器容易因挤压产生微裂纹,一旦封装层破裂,外界空气中的水分和氧气会迅速侵入,与有机发光材料和金属电极发生化学反应,导致发光点失效形成黑斑,并可能损坏内部电路,造成亮线、闪烁甚至屏幕完全失效等永久性的显示不良
相对于现有技术,本发明具有以下有益效果:本发明提供了一种OLED显示器微裂纹的修复材料及修复工艺,通过修复材料的配方与工艺协同作用,实现OLED显示器微裂纹的修复与水氧阻隔:
Abstract
Description
Technical Field
[0001] This invention belongs to the field of repair technology, specifically relating to a material and process for repairing cracks in OLED displays. Background Technology
[0002] Currently, OLED displays are widely used due to their superior display performance. They typically have a sandwich structure consisting of an extremely thin organic light-emitting layer, precision circuitry, and sensitive metal electrodes, and rely on thin-film encapsulation to isolate them from the external environment. However, in practical use, OLED displays are prone to microcracks due to pressure. Once the encapsulation layer breaks, moisture and oxygen from the outside air can quickly penetrate, reacting chemically with the organic light-emitting materials and metal electrodes. This causes the light-emitting points to fail, forming black spots, and may damage the internal circuitry, resulting in permanent display defects such as bright lines, flickering, or even complete screen failure. Existing technologies lack effective repair solutions to fill these microcracks and provide long-term protection against water and oxygen intrusion, leading to a shortened lifespan for OLED displays. Summary of the Invention
[0003] To address at least one of the aforementioned problems, this invention provides an OLED display crack repair material and repair process, which can effectively fill and seal microcracks, thereby blocking water and oxygen and protecting internal components.
[0004] To achieve the above objectives, the present invention employs the following technical means: The first aspect of the present invention provides an OLED display crack repair material, wherein the repair material comprises, by mass percentage: 60%-70% epoxy resin, 20%-30% inorganic filler, 5%-8% curing agent and 1%-2% coupling agent, wherein the inorganic filler is a mixture of nano-sized silica and aluminum nitride.
[0005] In some embodiments of the present invention, the inorganic filler is a mixture of nano-sized silica with a particle size of 5-20 nm and aluminum nitride with a particle size of 10-30 nm; in some embodiments of the present invention, the mass ratio of nano-sized silica to aluminum nitride is 1:1.
[0006] In some embodiments of the present invention, the curing agent is a modified amine curing agent. In some embodiments of the present invention, the curing agent is a polyetheramine.
[0007] In some embodiments of the present invention, the coupling agent is a silane coupling agent. In some embodiments of the present invention, the silane coupling agent is KH-550.
[0008] A second aspect of the present invention provides a crack repair process for an OLED display, comprising the following steps: S1. Wipe the surface of the OLED display panel to be repaired with isopropanol solution to remove dust, oil and other impurities, and then dry it. S2. Pour the repair material into the storage tank of the vacuum coating equipment; place the pre-treated panel into the vacuum coating equipment and draw a vacuum; use the coating mechanism of the vacuum coating equipment to evenly coat the repair material on the panel surface and the micro-crack area. S3. After coating is completed, keep the panel in the vacuum equipment for 5-10 minutes; then slowly introduce dry nitrogen into the vacuum equipment and gradually restore the pressure inside the equipment to atmospheric pressure at a rate of 0.02-0.05 MPa / min. S4. Remove the panel that has been sealed under atmospheric pressure from the vacuum equipment and place it in a curing oven for curing.
[0009] In some embodiments of the present invention, in step S1, the drying temperature is 40-50°C and the drying time is 10-30 minutes.
[0010] In some embodiments of the present invention, in step S2, the vacuum level inside the device is 1×10⁻⁶. -3 -5×10 -3 Pa.
[0011] In some embodiments of the present invention, in step S2, the coating speed of the coating mechanism is 5-10 mm / s, and the coating thickness is 5-10 μm.
[0012] In some embodiments of the present invention, in step S4, the curing temperature is ≤100℃ and the curing time is 30-40 minutes.
[0013] Beneficial effects of the present invention Compared with existing technologies, the present invention has the following beneficial effects: The present invention provides a repair material and repair process for microcracks in OLED displays. Through the synergistic effect of the repair material formulation and process, the repair of microcracks in OLED displays and water and oxygen barrier functions are achieved. During the vacuum coating stage, the vacuum environment eliminates the air pressure within the microcracks of the panel, allowing the repair material to penetrate smoothly into the microcracks and fill the gaps under the action of its own fluidity and the coating pressure of the equipment. Subsequently, during the atmospheric pressure sealing stage, the slowly recovering atmospheric pressure exerts a uniform squeezing effect on the repair material on the panel surface and within the microcracks, prompting the material to further compact and fill the cracks, eliminating the gaps between the material and the crack walls. After the material has cured, it forms a closed structure that is tightly bonded to the panel substrate, completely blocking the path of microcracks as a channel for water and oxygen intrusion. The cured repair material forms a dense composite structure of organic matrix and inorganic filler. The epoxy resin organic matrix forms a continuous polymer network, which can block the diffusion of water and oxygen molecules through the steric hindrance effect of the molecular chains. Nano-silica and aluminum nitride inorganic fillers are uniformly dispersed in the organic matrix. On the one hand, the dense crystal structure of the inorganic fillers themselves prevents the penetration of water and oxygen molecules. On the other hand, the presence of inorganic fillers prolongs the diffusion path of water and oxygen molecules inside the material, significantly reducing the penetration rate of water and oxygen molecules. At the same time, the coupling agent improves the interfacial bonding between the inorganic filler and the organic matrix, eliminates the gaps at the interface, and prevents water and oxygen molecules from penetrating through the interfacial gaps. This effectively protects the internal components of the OLED display and prevents picture defects caused by water and oxygen intrusion. Detailed Implementation
[0014] The following examples are used to illustrate preferred embodiments of the invention. Those skilled in the art will understand that the techniques disclosed in the examples represent techniques discovered by the inventors that can be used to implement the invention, and therefore can be considered preferred embodiments for implementing the invention. However, those skilled in the art should understand from this specification that many modifications can be made to the specific embodiments disclosed herein, still yielding the same or similar results, without departing from the spirit or scope of the invention.
[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains, and all materials disclosed herein and cited therein are incorporated herein by reference. Many equivalent techniques of specific embodiments of the invention described herein will be recognized or can be understood by ordinary experimentation by those skilled in the art. These equivalents will be included in the claims.
[0016] An OLED display crack repair material, comprising the following components by mass percentage: 60%-70% epoxy resin, 20%-30% inorganic filler, 5%-8% modified amine curing agent, and 1%-2% silane coupling agent. The inorganic filler is a mixture of nano-sized silica and aluminum nitride. Specifically, the inorganic filler is a mixture of nano-sized silica with a particle size of 5-20 nm and aluminum nitride with a particle size of 10-30 nm in a mass ratio of 1:1.
[0017] Epoxy resin, as the matrix component of the repair material, forms a three-dimensional network structure through a curing reaction, providing basic mechanical support and bonding properties for the repair material, ensuring that the repair material can firmly adhere to the crack wall of the OLED panel.
[0018] The inorganic filler is a mixture of nano-sized silica and aluminum nitride. Its main function is to fill the free volume in the epoxy resin matrix and form a bridging effect to block the diffusion of water and oxygen molecules. Silica has excellent chemical stability and hardness, which can increase the wear resistance of the repair material; while aluminum nitride not only has good insulation properties but also excellent thermal conductivity, which can quickly conduct away the local heat generated during the operation of the OLED display, avoiding aging of the repair material or interface delamination caused by heat accumulation. The combination of the two can simultaneously achieve mechanical strength, water and oxygen barrier properties, and heat dissipation performance.
[0019] The width of microcracks on OLED display panels is typically in the micrometer or even nanometer range. If the particle size of the inorganic filler is too large, it will be difficult for it to penetrate smoothly into the interior of the microcrack along with the epoxy resin matrix. It is easy to form a bridging effect at the crack opening, resulting in voids in the deep part of the crack. If the particle size is too small, although the permeability is improved, the specific surface area of the inorganic filler increases sharply, and the surface energy is too high. It is very easy for it to agglomerate in the resin matrix, which will cause uneven dispersion and form stress concentration points.
[0020] The role of the curing agent is to undergo a cross-linking reaction with the epoxy resin, connecting the linear epoxy resin molecular chains into a network structure. The amount of curing agent used needs to be matched with the epoxy equivalent of the epoxy resin. If the curing agent content is too low, curing will be incomplete, leaving unreacted epoxy groups in the material, leading to a decrease in material strength and a deterioration in chemical corrosion resistance. If the curing agent content is too high, excess curing agent may remain free in the matrix, forming a weak interfacial layer, which will also reduce the overall performance of the material.
[0021] Coupling agents, as interfacial modifiers, typically contain two functional groups with different properties in their molecular structure. One functional group reacts chemically or physically with the surface of inorganic fillers, while the other reacts or entangles with the organic matrix. Through the action of coupling agents, the dispersibility of inorganic fillers in epoxy resin matrices can be significantly improved, and the interfacial bonding force between inorganic fillers and the organic matrix can be enhanced.
[0022] Through the synergistic effect of the above components, the repair material of this embodiment can form a dense composite structure of organic matrix and inorganic filler, which can effectively fill microcracks while blocking the intrusion of external water and oxygen in a long-term stable manner, thus protecting the internal components of the OLED display from damage.
[0023] A crack repair process for OLED displays includes the following steps: S1. Wipe the surface of the OLED display panel to be repaired with isopropanol solution to remove dust, oil and other impurities, and then dry it; the drying temperature is 40-50℃ and the drying time is 10-30 minutes. S2. Pour the repair material into the storage tank of the vacuum coating equipment; place the pre-treated panel into the vacuum coating equipment, and evacuate the equipment to a vacuum level of 1×10⁻⁶. -3 -5×10 -3 Pa; The repair material is uniformly coated on the panel surface and micro-crack areas using the coating mechanism of the vacuum coating equipment; the coating speed of the coating mechanism is 5-10 mm / s, and the coating thickness is 5-10 μm; S3. After coating is completed, keep the panel in the vacuum equipment for 5-10 minutes; then slowly introduce dry nitrogen into the vacuum equipment and gradually restore the pressure inside the equipment to atmospheric pressure at a rate of 0.02-0.05 MPa / min. S4. Remove the panel that has been sealed under atmospheric pressure from the vacuum equipment and place it in a curing oven for curing; curing temperature ≤100℃, curing time 30-40 minutes.
[0024] The technical solution of this application will be further described in detail below with reference to specific embodiments.
[0025] Example 1 An OLED display crack repair material, the material is composed of the following components by mass percentage: 70% epoxy resin, 23% inorganic filler, 5% polyetheramine and 2% KH-550, wherein the inorganic filler is a mixture of 10nm nano-sized silica and 15nm aluminum nitride in a mass ratio of 1:1.
[0026] A crack repair process for OLED displays includes the following steps: S1. Wipe the surface of the OLED display panel to be repaired with isopropanol solution to remove dust, oil and other impurities, and then dry it; the drying temperature is 50℃ and the drying time is 15 minutes. S2. Pour the repair material into the storage tank of the vacuum coating equipment; place the pre-treated panel into the vacuum coating equipment, and evacuate the equipment to a vacuum degree of 3×10⁻⁶. -3 Pa; The repair material is uniformly coated on the panel surface and micro-crack areas using the coating mechanism of the vacuum coating equipment; the coating speed of the coating mechanism is 10 mm / s, and the coating thickness is 10 μm; S3. After coating is completed, keep the panel stationary in the vacuum equipment; then slowly introduce dry nitrogen into the vacuum equipment, gradually restoring the pressure inside the equipment to atmospheric pressure at a rate of 0.05 MPa / min. S4. Remove the panel that has been sealed under atmospheric pressure from the vacuum equipment and place it in a curing oven for curing; curing temperature ≤100℃, curing time 30 minutes.
[0027] Example 2 An OLED display crack repair material, comprising the following components by mass percentage: 60% epoxy resin, 30% inorganic filler, 8% polyetheramine, and 2% KH-550. The inorganic filler is a mixture of nano-sized silica and aluminum nitride. Specifically, the inorganic filler is a mixture of 10nm nano-sized silica and 30nm aluminum nitride in a mass ratio of 1:1.
[0028] A crack repair process for OLED displays includes the following steps: S1. Wipe the surface of the OLED display panel to be repaired with isopropanol solution to remove dust, oil and other impurities, and then dry it; the drying temperature is 50℃ and the drying time is 20 minutes. S2. Pour the repair material into the storage tank of the vacuum coating equipment; place the pre-treated panel into the vacuum coating equipment, and evacuate the equipment to a vacuum level of 1×10⁻⁶. -3 Pa; The repair material is uniformly coated on the panel surface and microcrack areas using the coating mechanism of the vacuum coating equipment; the coating speed of the coating mechanism is 6 mm / s, and the coating thickness is 8 μm; S3. After coating is completed, keep the panel in the vacuum equipment for 10 minutes; then slowly introduce dry nitrogen into the vacuum equipment and gradually restore the pressure inside the equipment to atmospheric pressure at a rate of 0.05 MPa / min. S4. Remove the panel that has been sealed under atmospheric pressure from the vacuum equipment and place it in a curing oven for curing; curing temperature ≤100℃, curing time 30 minutes.
[0029] Example 3 An OLED display crack repair material, comprising the following components by mass percentage: 65% epoxy resin, 28% inorganic filler, 6% polyetheramine and 1% KH-550. The inorganic filler is a mixture of nano-sized silica with a particle size of 20nm and aluminum nitride with a particle size of 10nm in a mass ratio of 1:1.
[0030] A crack repair process for OLED displays includes the following steps: S1. Wipe the surface of the OLED display panel to be repaired with isopropanol solution to remove dust, oil and other impurities, and then dry it; the drying temperature is 40℃ and the drying time is 30 minutes. S2. Pour the repair material into the storage tank of the vacuum coating equipment; place the pre-treated panel into the vacuum coating equipment, and evacuate the equipment to a vacuum degree of 5×10⁻⁶. -3 Pa; The repair material is uniformly coated on the panel surface and micro-crack areas using the coating mechanism of the vacuum coating equipment; the coating speed of the coating mechanism is 5 mm / s, and the coating thickness is 10 μm; S3. After coating is completed, keep the panel stationary in the vacuum equipment; then slowly introduce dry nitrogen into the vacuum equipment, gradually restoring the pressure inside the equipment to atmospheric pressure at a rate of 0.02 MPa / min. S4. Remove the panel that has been sealed under atmospheric pressure from the vacuum equipment and place it in a curing oven for curing; curing temperature ≤100℃, curing time 35 minutes.
[0031] The panels repaired in Examples 1-3 above were tested and found to show no black spots, bright lines or other display defects after being placed in a high temperature and high humidity environment (85℃ / 85%RH) for 1000 hours. The repair material was firmly bonded to the panel substrate, with no delamination or peeling, demonstrating excellent water and oxygen barrier properties and long-term stability.
[0032] In the above embodiments, epoxy resin is used as the organic matrix, which has good adhesion, chemical stability and mechanical strength, and can form a strong bond with the substrate of the OLED display panel. At the same time, the cross-linking curing characteristics of epoxy resin can form a continuous and dense polymer network structure, providing a basic framework for water and oxygen barrier and effectively blocking the penetration of water and oxygen molecules.
[0033] The inorganic fillers used are nano-sized silica particles with a diameter controlled at 5-20 nm and aluminum nitride particles with a diameter controlled at 10-30 nm. This dual-particle-size gradation design, through the gradation of inorganic fillers with different particle sizes, allows smaller particles to fill the gaps between larger particles, thereby constructing a denser inorganic network structure within the epoxy resin matrix. This further extends the diffusion path of water and oxygen molecules, significantly improving the density and barrier properties of the repair material. Aluminum nitride not only has excellent water and oxygen barrier properties but also superior thermal conductivity, which can effectively conduct away the heat generated during OLED display operation, preventing localized high temperatures from affecting material performance and display lifespan.
[0034] Modified amine curing agent polyetheramine has lower viscosity and good compatibility with epoxy resins. Its low viscosity facilitates rapid flow of the material under capillary forces and atmospheric pressure. The flexible polyether segments in the polyetheramine molecule structure give the cured repair material a certain degree of flexibility, which can buffer the internal stress generated by thermal expansion and contraction of OLED displays during operation, preventing the repair material from becoming brittle and causing seal failure. Simultaneously, polyetheramine has a moderate curing reaction rate, initiating cross-linking reactions at low temperatures. This effectively avoids the formation of bubbles inside the material due to excessive heat release during curing, or thermal damage to the sensitive organic light-emitting layer inside the OLED panel due to violent exothermic reactions. Using polyetheramine as a curing agent, complete curing can be achieved at temperatures not exceeding 100°C, and the cured material surface is smooth and bubble-free, demonstrating excellent process adaptability.
[0035] The silane coupling agent KH-550 has groups at both ends of its molecule that react with inorganic fillers and organic matrices, respectively. One end can chemically react with the hydroxyl groups on the surface of inorganic fillers such as nano-silica and aluminum nitride to form strong Si-O-Si or Si-O-Al chemical bonds. The other end can react with the epoxy groups of epoxy resin, enhancing the interfacial bonding force between inorganic fillers and organic matrices, improving the dispersibility of fillers in the matrix, reducing interfacial defects, significantly enhancing the interfacial bonding force between inorganic fillers and organic matrices, eliminating microscopic voids at the interface, and further improving the compactness and water and oxygen barrier properties of the material. The solution proposed in this application optimizes and combines the particle size of inorganic fillers, the type of curing agent, and the type of coupling agent, enabling the repair material to achieve deep filling and long-term sealing of microcracks while maintaining good operability. The organic-inorganic interpenetrating network structure formed after curing is dense and defect-free, which can effectively resist long-term erosion by external water and oxygen, thereby achieving the repair of microcracks in OLED displays and water and oxygen barrier, and significantly extending the service life of the repaired OLED displays.
[0036] Comparative Example 1 The repair process used in this solution is the same as that in Example 3, except that the repair material used has the following composition by mass percentage: 75% epoxy resin, 15% inorganic filler, 5% curing agent and 5% other additives. The inorganic filler is only nano-sized silica and does not contain aluminum nitride.
[0037] The results showed that after the repaired panel was placed in a high temperature and high humidity environment (85℃ / 85%RH) for 500 hours, slight black spots appeared.
[0038] The reason may be that the inorganic filler content in the repair material is too low, which makes it unable to form an effective barrier network; and the lack of thermal conductivity of aluminum nitride causes the repair material to age locally due to heat accumulation during panel operation, resulting in a decrease in interfacial bonding force, and water and oxygen molecules can penetrate into the interior of the panel along the interface.
[0039] Comparative Example 2 The repair materials and repair process used in this solution are the same as those in Example 3. The difference is that the atmospheric pressure sealing process in step S3 is omitted in the repair process. That is, after vacuum coating is completed, the panel is directly taken out of the vacuum equipment for curing.
[0040] The results showed that after the repaired panel was placed in a high-temperature and high-humidity environment (85℃ / 85%RH) for 300 hours, obvious black spots and bright lines appeared. Microscopic observation revealed that the repair material within the microcracks contained obvious voids and air bubbles, and there were gaps between the material and the crack walls.
[0041] The reason may be the lack of the compression effect of the atmospheric pressure sealing step. The repair material can only penetrate into the crack by vacuum negative pressure, which cannot achieve dense filling. The micro gaps left between the material and the crack wall become channels for water and oxygen to penetrate, resulting in repair failure.
[0042] Comparative Example 3 The repair materials and repair process used in this solution are the same as those in Example 3, except that the curing temperature is increased to 120°C.
[0043] The results showed that the repaired panel exhibited slight uneven brightness immediately after curing, and the uneven brightness gradually worsened with prolonged use.
[0044] The reason may be that the curing temperature was too high, causing partial thermal degradation of the organic light-emitting layer inside the OLED display, reducing the interfacial bonding force between the metal electrode and the organic layer, and affecting the display performance. This comparative example fully illustrates the necessity and importance of the low-temperature curing process (≤100℃) used in this invention.
[0045] In summary, this invention provides an OLED display crack repair material and repair process. The epoxy resin, inorganic filler, curing agent, and coupling agent in the repair material form an organic-inorganic composite dense structure, effectively blocking the penetration of water and oxygen molecules. The repair process combines vacuum coating with atmospheric pressure sealing to ensure that the repair material fully penetrates the microcracks and achieves dense filling. The low-temperature curing process avoids thermal damage to the internal components of the OLED display. The overall solution achieves deep filling and long-term sealing of microcracks in OLED displays through the synergistic combination of the specific formulation of the repair material and the repair process.
[0046] All documents mentioned in this invention are incorporated herein by reference as if each document were individually incorporated by reference. Furthermore, it should be understood that after reading the foregoing teachings of this invention, those skilled in the art can make various alterations or modifications to this invention, and these equivalent forms also fall within the scope defined by this application.
Claims
1. A crack repair material for OLED displays, characterized in that, The repair material comprises the following components by mass percentage: 60%-70% epoxy resin, 20%-30% inorganic filler, 5%-8% curing agent, and 1%-2% coupling agent. The inorganic filler is a mixture of nano-sized silica and aluminum nitride.
2. The OLED display crack repair material according to claim 1, characterized in that, The inorganic filler is a mixture of nano-sized silica with a particle size of 5-20 nm and aluminum nitride with a particle size of 10-30 nm.
3. The OLED display crack repair material according to claim 1, characterized in that, The curing agent is a modified amine curing agent.
4. The OLED display crack repair material according to claim 3, characterized in that, The curing agent is polyetheramine.
5. The OLED display crack repair material according to claim 1, characterized in that, The coupling agent is a silane coupling agent.
6. A crack repair process for OLED displays, characterized in that: Includes the following steps: S1. Wipe the surface of the OLED display panel to be repaired with isopropanol solution to remove dust, oil and other impurities, and then dry it. S2. Pour the repair material into the storage tank of the vacuum coating equipment; place the pre-treated panel into the vacuum coating equipment and draw a vacuum; use the coating mechanism of the vacuum coating equipment to evenly coat the repair material on the panel surface and the micro-crack area. S3. After coating is completed, keep the panel stationary in the vacuum equipment; then slowly introduce dry nitrogen into the vacuum equipment, gradually restoring the pressure inside the equipment to atmospheric pressure at a rate of 0.02-0.05 MPa / min. S4. Remove the panel that has been sealed under atmospheric pressure from the vacuum equipment and place it in a curing oven for curing.
7. The OLED display crack repair process according to claim 6, characterized in that: In step S1, the drying temperature is 40-50℃ and the drying time is 10-30 minutes.
8. The OLED display crack repair process according to claim 6, characterized in that: In step S2, the vacuum level inside the equipment is 1×10⁻⁶. -3 -5×10 -3 Pa.
9. The OLED display crack repair process according to claim 6, characterized in that: In step S2, the coating speed of the coating mechanism is 5-10 mm / s, and the coating thickness is 5-10 μm.
10. The OLED display crack repair process according to claim 6, characterized in that: In step S4, the curing temperature is ≤100℃ and the curing time is 30-40 minutes.